Psychological support for sport coaches: an exploration of practitioner psychologist perspectives - Kelly, S.; Thelwell, R.; Barker, J. B.; Harwood, C. G. (Journal of Sports Sciences, 2018)
In the present study we add to the literature by exploring the degree to which UK practitioner psychologists perceive themselves able to support sport coaches, and how professional training prepares psychologists for coach work across performance domains. Ten participants comprising seven sport and exercise psychologists with Health Care Professions Council (HCPC) practitioner psychologist status and three trainee psychologists studying towards the British Psychological Society (BPS) qualification in sport and exercise psychology (QSEP) were individually interviewed. All participants reported prior experience of working with coaches across all performance domains. We explored: practitioner`s understanding of the challenges coaches face within their job; practitioner`s experiences of coach work; perspectives about the ways in which practitioners could and should support coaches; and, the degree to which professional training prepares practitioners for coach work. Using recommended procedures of Connelly and Peltzer, content analysis revealed practitioners perceived the challenges faced by coaches are different at grassroots level compared to those working with elite athletes, and that practitioners require skills to provide one-to-one coach support and group-based interventions. All practitioners perceived that training programmes do not adequately equip trainees with skills required for coach work. We discuss the implications for enhancing practitioner training in the UK.